Rescuing Canavan Disease by Redirecting Metabolic Processing: Support for the Astrocyte Hypothesis of Canavan Disease Generation and A Possible Human Cure - H Baslow, Morris; N Guilfoyle, David (Journal of Glycomics And Metabolism, 2017)
Canavan disease (CD) is a globally occurring but rare human spongiform leukodystrophy that is associated with inborn errors affecting the activity of aspartoacylase (ASPA), an enzyme highly expressed in oligodendrocytes that hydrolyzes N-acetylaspartate (NAA). Lack of ASPA activity is associated with the inability of oligodendrocytes to build or maintain axon-enveloping myelin sheaths. The primary source of NAA in brain is neurons, cells that synthesize but cannot catabolize it. Neurons also synthesize N-acetylaspartylglutamate (NAAG) from NAA and glutamate but cannot catabolize this substance as well. For their metabolism, these substances are released to extracellular fluid and are metabolized by oligodendrocyte ASPA and astrocyte NAAG peptidase respectively. A hypothesis developed suggested that the cause of the leukodystrophy component in CD was due to release of NAAG by neurons at white matter nodes of Ranvier, its catabolism by astrocytes forming NAA and increased osmotic-hydrostatic pressure as a result of its buildup at these nodes due to the lack of ASPA activity. In this communication, we provide evidence supporting this hypothesis and comment on the cause and possible cure for human CD.
Keywords: N-acetylaspartate; N-acetylaspartylglutamate; aspartoacylase; astrocytes; Canavan disease; leukodystrophy